Incumplimiento de las obligaciones internacionales del estado ecuatoriano durante los amotinamientos en el año 2021 - Morocho Gonzaga, Vanessa Lisbeth (2024)
The purpose of this study is to assess whether the Ecuadorian State fulfills its role as protector of the rights of persons deprived of liberty, particularly during the riots that occurred in the Social Rehabilitation Centers in 2021. To achieve this, a qualitative approach is employed that includes interviews and surveys of experts and people involved in the social rehabilitation system. The analysis focuses on the crisis that Social Rehabilitation Centers have experienced in recent years, which makes it possible identify situations for risk persons deprived of liberty in Ecuador. The results indicate a clear violation of rights, with the State assuming responsibility in cases that resulted in harm to physical and integrity, psychological or fundamental rights.